Studi Eksperimental Pengaruh Variasi Parameter Perlakuan Panas terhadap Kekerasan Baja Tulangan Polos BJTP280 - Imam Rudi Sugara; Dwi Wahyu Hardiyanto; Faizah Ali; Elvira Wahyu Arum Fanani (Yayasan Literasi Sains Indonesia, 2025)
The construction and manufacturing industries require materials with optimal mechanical properties, particularly hardness and toughness. BJTP280 structural steel, classified as low-carbon steel, has the potential to enhance its mechanical properties through heat treatment. This study aims to analyze the effect of variations in austenitizing temperature, holding time, and cooling medium on the hardness and microstructure of the steel. Specimens measuring 10 × 8 mm were heated at temperatures of 750°C, 800°C, and 850°C with holding times of 60, 90, and 120 minutes, followed by cooling in air, oil, and water. Hardness tests were conducted using the Brinell method, while the microstructure was observed with an optical microscope. The results showed that the cooling medium had a significant effect. The highest hardness values were obtained with water quenching at 178 HB, oil quenching at 174 HB, and air cooling at 144 HB. Hardness tended to decrease with increasing holding time due to austenite grain growth. An austenitizing temperature of 800°C produced the optimum condition with the highest hardness value, while 850°C resulted in lower hardness because of excessively coarse grain structures. In conclusion, the best heat treatment was achieved at 800°C, water quenching, and a holding time of 60 minutes.